Acceleration in linear growth after splenectomy for hypersplenism in homozygous sickle cell disease. Issue 3 (March 1995) - Singhal, A; Thomas, P; Kearney, T; Venugopal, S; Serjeant, G
Abstract : Chronic hypersplenism in homozygous sickle cell (SS) disease markedly increases haemolysis and the resulting erythropoietic expansion is likely to have a high metabolic cost. Splenectomy for hypersplenism in SS disease is followed by highly significant changes in haematological indices and an increase in height, but not weight, velocity. This pattern is similar to that observed in the trichuris dysentery syndrome after treatment, and differs from the increases in both height and weight velocity that follow nutritional supplementation of severely malnourished children. It is postulated that accelerated linear growth after the reduction in erythropoietic stress may implicate a specific nutrient deficiency in hypersplenic children with SS.